2015
DOI: 10.1016/j.arth.2015.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Benefits Total Joint Arthroplasty Patients Regardless of Preoperative Hemoglobin Value

Abstract: While tranexamic acid (TXA) reduces transfusion in total joint arthroplasty (TJA), it remains unclear whether there is a preoperative hemoglobin (Hgb) threshold above which it is no longer beneficial. 2100 primary TJA patients were retrospectively categorized by preoperative Hgb; 1161 (55%) received TXA. Transfusion rates decreased with TXA in all groups; with Hgb>15 the transfusion rate was 0.5% with TXA and 4.5% without (P=0.0086); with Hgb>11 the transfusion rate was 4.7% with TXA and 18.7% without (P<0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…A recent meta-analysis showed IV TXA was effective in reducing allogenic blood transfusion by 50% and limiting blood loss intraoperatively and through drains in patients undergoing primary THA [27]. Whiting et al [43] recently reported that TXA may be beneficial in patients undergoing total joint arthroplasty regardless of preoperative Hgb, with patients with anemia still seeing transfusion reductions. Similar findings also were reported by Phan et al [35] who found no difference in the risk of transfusion between patients with anemia (Hgb\12 g/dL) versus those without anemia undergoing THA and receiving TXA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed IV TXA was effective in reducing allogenic blood transfusion by 50% and limiting blood loss intraoperatively and through drains in patients undergoing primary THA [27]. Whiting et al [43] recently reported that TXA may be beneficial in patients undergoing total joint arthroplasty regardless of preoperative Hgb, with patients with anemia still seeing transfusion reductions. Similar findings also were reported by Phan et al [35] who found no difference in the risk of transfusion between patients with anemia (Hgb\12 g/dL) versus those without anemia undergoing THA and receiving TXA.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8,11,15,19,20 TXA has been shown to reduce blood loss and transfusion rates after TKA 1,3,5,9,12 as well as in other surgical procedures such as rhinoplasty. 21 The use of TXA was shown not to cause any extra complication such as thromboembolic events and renal dysfunction in a study using the data of 872,416 patients, 19 and it was also reported to be safe for patients with severe comorbidities in elective arthroplasty surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…7 TXA has been shown to reduce transfusion rates in patients with a haemoglobin level higher than 15 g/dl, so it should be considered in all total joint arthroplasty patients independent of preoperative haemoglobin level. 8 Despite an increased drug cost with the use of TXA in healthy patients, concomitant reductions in operating room, blood/laboratory and room costs have been shown to contribute to nearly $900 (USA Dollar) cost savings. 22 TXA has been in routine use in total joint arthroplasty during the last decade with the benefits of decreasing blood loss, transfusion rates and hospital costs without any increase in complication rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nowadays the specific method is likely to be used under certain circumstances. 35 Intraoperative administration of TXA has been shown to be a method of blood loss reduction during TKR, as well as reducing allogeneic transfusion even in anemic patients. We first mentioned that TXA was associated with a low risk of symptomatic thromboembolic events when used with three different chemical prophylactic regimens after routine primary TKA.…”
Section: Discussionmentioning
confidence: 99%